2000
DOI: 10.1007/s11663-000-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Melt flow control in a multistrand tundish using a turbulence inhibitor

Abstract: Water modeling and mathematical simulation techniques were used to study the melt flow under the influence of turbulence inhibitors in a multistrand bloom caster tundish. Three different cases were studied: a bare tundish (BT), a tundish with two pairs of baffles and a waved impact pad (BWIP), and a tundish equipped with turbulence inhibitor and a pair of dams (TI&D). Chemical mixing of tracer turbulence diffusion was also simulated and compared with actual experimental results. The TI&D arrangement showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…The flow rate is larger than in the steady state in order to recover the standard amount of molten steel in the tundish. The fourth phase (Phase [4]) is the steady state of the new ladle. The flow rate from the new ladle to the tundish and the amount of molten steel in the tundish have both returned to the steady state values.…”
Section: Physical Description Of Ladle Change Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow rate is larger than in the steady state in order to recover the standard amount of molten steel in the tundish. The fourth phase (Phase [4]) is the steady state of the new ladle. The flow rate from the new ladle to the tundish and the amount of molten steel in the tundish have both returned to the steady state values.…”
Section: Physical Description Of Ladle Change Operationmentioning
confidence: 99%
“…1,2) Sahai's method is useful in quantitatiion of the flow characteristics of tundishes, and thus is commonly used by the authors. [3][4][5][6][7][8] It has also been reported that the characteristic volumes, in particular the plug-flow volume, have a relation to inclusion removal performance in steady state tundishes. 9,10) Particle injection is also a popular method for direct investigation of inclusion removal performance in tundishes.…”
Section: Introductionmentioning
confidence: 98%
“…RTD curve analysis models for multi-strand tundishes were mainly worked out on the basis of the combined model. [3][4][5][6][7][8][9][10][11][12] Pulse stimulus-response method was often adopted to obtain the outlet tracer concentration versus time curve (C curve) in simulation experiment of multi-strand tundishes. Then C curve was analyzed or translated into E curve.…”
Section: Fluid Flow Characterization In Asymmetric Tundishmentioning
confidence: 99%
“…The volume fraction of plug, mixed and dead regions is the sum of that of plug, mixed and dead regions of different strands. R. D. Morales,5) A. Kumar [10][11][12] and H. Lei 13) used the experiment data of different strands of multi-strand tundishes to calculate the overall RTD curve, then analyzed the RTD curve using the combined model, and finally evaluated the flow characteristics. However, if the combined model is used to calculate the RTD curves of different outlets, there may exist negative volume fraction of dead region or bigger calculation errors.…”
Section: Fluid Flow Characterization In Asymmetric Tundishmentioning
confidence: 99%
“…Morales et al [14] used water modeling and mathematical simulation techniques to conclude that the presence of turbulenceinhibitors increases product quality in a four-strand bloom caster tundish. Zhang et al [15] calculated the inclusion removal in a single-strand tundish with and without flow modifiers.…”
Section: Introductionmentioning
confidence: 99%